Simple, Scalable Route to Produce Transparent Superhydrophobic/Hydrophilic Film Surfaces - Shroq AlZadjali; Zineb Matouk; Abdulla AlShehhi; Nitul Rajput; Meriam Mohammedture; Monserrat Guttierrez (Applied Sciences, 2023)
Superhydrophobic coatings are gaining popularity because of their low maintenance requirements, high durability, and wide range of potential uses. Such coatings, for instance, may provide beneficial resistance to fouling, icing, smear, and corrosion, and can separate oil from water. Therefore, the creation of superhydrophobic materials is a topic of great interest to academics all around the world. In this paper, a spray-coating deposition technique is used to deposit silica nanoparticles on glass while using a sol–gel as a base. The applied coating increased the transmittance to 99% at 600 nm. Water contact angle (WCA) and scanning electron microscopy (SEM) observations of the coated layer’s grade index and induced porousness led to superhydrophobic behavior with a water contact angle that was higher than 158°.